Translation Studies in Indonesian Subtitle Translated by Pein Akatsuki of a Film Frozen II 2019 - Qawaid, Farhanah Adhiyanih; Rijal, Andi Samsu; Khalik, Fihris (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2025)
Translation plays a crucial role in many aspects, including film subtitles. This research aimed toidentify the types of translation strategies and the quality of the translations used in the Indonesian subtitle ofthe film Frozen II. Using a descriptive qualitative method, the analysis was based on Suryawinata and Hariyanto'stranslation strategies classification, which includes structural and semantic strategies. Nine strategies wereidentified: addition, transposition, borrowing, cultural equivalent, descriptive equivalent, synonym, reduction,expansion, and modulation. The translation's quality was evaluated using Nababan et al.'s criteria of accuracy,acceptability, and readability. The results showed that the translation was highly accurate, with an accuracypercentage of 85.9%. However, the 14.1% of translations classified as less accurate (12.7%) or inaccurate(1.4%) highlight challenges in capturing nuance, tone, and context, often due to constraints like limited spaceand timing in subtitles. While most translations were accurate, these cases emphasize the need for carefulattention to detail to maintain the original meaning. Furthermore, this study concludes that the translatoreffectively applied multiple strategies, resulting in a high-quality translation that captures the intended meaningand cultural nuances of Frozen II. Additionally, the distinct contribution of this study lies in its thoroughintegration of both structural and semantic translation strategies, providing a more comprehensive analysisthan previous research. It emphasizes the critical importance of not only translating language accurately butalso conveying meaning and cultural nuances, particularly in the subtitles of animated films, to preserve theoriginal essence and emotional impact for Indonesian audiences.